The Analysis of Plot in The Novel In His Father’s Footsteps by Danielle Steel - Dian Oktapiana, Dewa Ayu (Udayana Journal of Social Sciences and Humanities; Vol 7 No 1 (2023): UJoSSH, February 2023, 2023)
This study is an analysis of Danielle Steel work entitled In His Father's Footsteps that has a historical setting before the World War II, when the Buchenwald concentration camp operated until the three generations of family's life after being liberated from Buchenwald and starting life as an immigrant which is settling in America. This data is the main data source that discusses how Danielle Steel composes the storyline and presents conditions in it. The nature of this study is literary analysis with descriptive qualitative approach to answer the problems posed. In completing the problem formulation in this study, the type of plot using Russell's (1991) theory in the kind of episode plot types. The plot structure using DiYanni's (2006) theory which is classified into exposition, complication, climax, falling action, and resolution. The results of this study discuss how Danielle Steel arranges the plot in a progressive manner as well as the storyline that shows.